# SOLUTION: Solve ( x2 – 2x )( x + 3) = -2x ( x + 1)

Algebra ->  Algebra  -> Quadratic Equations and Parabolas -> SOLUTION: Solve ( x2 – 2x )( x + 3) = -2x ( x + 1)       Log On

 Ad: You enter your algebra equation or inequality - Algebrator solves it step-by-step while providing clear explanations. Free on-line demo . Ad: Algebra Solved!™: algebra software solves algebra homework problems with step-by-step help! Ad: Algebrator™ solves your algebra problems and provides step-by-step explanations!

 Quadratics: solvers Practice! Answers archive Lessons Word Problems In Depth

 Click here to see ALL problems on Quadratic Equations Question 167559: Solve ( x2 – 2x )( x + 3) = -2x ( x + 1) Answer by sowmya(32)   (Show Source): You can put this solution on YOUR website!( x2 – 2x )( x + 3) = -2x ( x + 1) x(x-2)(x+3)=-2x(x+1) x(x-2)(x+3)+2x(x+1)=0 x{(x-2)(x+3)+2(x+1)}=0 x=0 or (x-2)(x+3)+2(x+1) =0 x^2+x-6+2x+2 = 0 x^2+3x-4=0 x^2+4x-x-4=0 (x-1)(x+4)=0 Hence the solutions are x=0, x=1 or x=-4